2017
DOI: 10.1016/j.bbrep.2017.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Computational study of the activity, dynamics, energetics and conformations of insulin analogues using molecular dynamics simulations: Application to hyperinsulinemia and the critical residue B26

Abstract: Due to the increasing prevalence of diabetes, finding therapeutic analogues for insulin has become an urgent issue. While many experimental studies have been performed towards this end, they have limited scope to examine all aspects of the effect of a mutation. Computational studies can help to overcome these limitations, however, relatively few studies that focus on insulin analogues have been performed to date. Here, we present a comprehensive computational study of insulin analogues—three mutant insulins th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 71 publications
0
11
0
Order By: Relevance
“…Specifically, the C-terminus of the B-chain of insulin behaves as a zipper and exhibits transitions between closed (inactive) to a wide-open (active) conformer to facilitate binding to IR. The conformational transitions, key residues, and the energetics of BC-CT were investigated using MD simulations ( 95 , 100 , 108 ). To probe the effect of varying pressure, temperature, pH, chemical modifications, and electric field on the structure of insulin, several MD studies were conducted ( 71 , 78 , 79 , 84 , 102 , 122 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, the C-terminus of the B-chain of insulin behaves as a zipper and exhibits transitions between closed (inactive) to a wide-open (active) conformer to facilitate binding to IR. The conformational transitions, key residues, and the energetics of BC-CT were investigated using MD simulations ( 95 , 100 , 108 ). To probe the effect of varying pressure, temperature, pH, chemical modifications, and electric field on the structure of insulin, several MD studies were conducted ( 71 , 78 , 79 , 84 , 102 , 122 ).…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that insulin strongly interacts with the nanosheets by its flexible C- and N-termini. The probability density function and the potential of mean force calculations were performed to understand the effects of mutations on the dynamics of the BC-CT opening and the energetics of insulin activation ( 108 ). Several studies revealed that BC-CT unzips from the hydrophobic core to facilitate binding of insulin to IR ( 40 , 95 , 165 167 ).…”
Section: Review Of Simulation Studies (1985 - To Date)mentioning
confidence: 99%
“…[1][2][3] Mature bioactive human insulin has been structurally well-characterized and is a 51 amino acid peptide consisting of two chains A and B held together by two inter-chain disulfide bridges and further stabilised by an intra-chain-A cysteine-bridge. [4][5][6][7][8] Insulin mediates a host of important metabolic functions through its engagement with the insulin receptor (IR). 1,4,9,10 The IR belongs to the receptor tyrosine kinase (RTK) family of receptors that include type 1 and 2 insulin like growth factor receptors (IGF1-and IGF-2R) and the orphan insulin receptor-related receptor.…”
Section: Introductionmentioning
confidence: 99%
“…4 These structures were complemented by computational studies that emphasised the importance of these domains for insulin binding. 6,7,[13][14][15] In 2018, single electron microscopy (EM) experiments have shown that activation of the insulin-IR complex involved transitioning from an inverted 'V' conformation to a T-like state that is thought to allow the transmembrane domains to come in proximity to each other and result in auto-phosphorylation and downstream signaling. 2 In the same year, Xu et al, resolved the structure of the IGF-1R bound to its cognate ligand the insulin-like growth factor (IGF), which revealed both similarities and differences with the IR-insulin complex.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation